PENDIDIKAN AKHLAK DALAM MEMBANGUN KARAKTER SISWA DI SEKOLAH: PENDIDIKAN AKHLAK DALAM MEMBANGUN KARAKTER SISWA DI SEKOLAH (PENDAIS, 2025)
Abstract Education at school is a learning activity      the main thing.  Which shows as a result whether or not achievement in education depends a lot on how the learning process is experienced by students as students Moral belief education in schools has a very important role in forming students' character. In Indonesia, character is an aspect that is given great attention to in learning, especially in the context of religious education which teaches moral, ethical and spiritual values. Moral belief education does not only lead to teaching about religious beliefs, but also about attitudes and behavior that reflect noble morals.